Antimalarial peptides: the long and the short of it - BELL, ANGUS (My University, 2011)
Antimicrobial peptides include a diverse array of both natural and synthetic molecules varying greatly in size, charge, hydrophobicity and secondary-structural features. Although better known as antibacterial agents, many peptides have demonstrated activity against the malarial parasite Plasmodium either in its vertebrate blood stages or mosquito stages or both. The antimalarial peptides reviewed here consist of (i) cationic, amphipathic 'host-defence' peptides including some (e.g. defensins and cecropins) that are naturally produced by mosquitos, (ii) other membrane-active peptide antibiotics such as gramicidins, (iii) hydrophobic peptides, most notably cyclosporins, (iv) thiopeptides, such as thiostrepton, and (v) some other naturally occurring or synthetic peptides. Many of these peptides affect membrane integrity and some are selective for parasite membranes over those of the host, while others are thought to have more specific intracellular targets. The mechanisms of action of the majority of antimalarial peptides are however either uncertain or totally unknown. Very few of these agents have been tested in rodent malaria models and none has undergone significant pre-clinical or clinical development for malaria. Issues such as metabolic lability, high cost, and a lack of information about systemic toxicity are likely to be serious obstacles to further development of peptides as antimalarial drugs. On the other hand, they offer potential advantages, including the possibility of being much less prone to resistance than the drugs in current use. An alternative to conventional chemotherapy, namely the release of malaria-refractory, transgenic mosquitos overproducing antimalarial peptides, has already passed the 'proof of concept' stage.
PUBLISHED
Keywords: Malaria, Plasmodium, antimalarial chemotherapy, antimicrobial peptide, gramicidin, cyclosporin, thiopeptide, haemoglobin degradation, Thiazolyl antibiotics, parasitaemia; Malaria, Plasmodium, antimalarial chemotherapy, antimicrobial peptide, gramicidin, cyclosporin, thiopeptide, haemoglobin degradation, Thiazolyl antibiotics, parasitaemia